An argument for using additional bedside tools, such as bedside ultrasound, for volume status assessment in hospitalized medical patients: A needs assessment survey. Issue 11 (11th September 2014) - Low, David; Vlasschaert, Meghan; Novak, Kerri; Chee, Alex; Ma, Irene W. Y.
<x xml:space="preserve">Abstract</x> The frequency at which housestaff need to assess volume status on medical inpatients is unknown. In this brief report, we invited 39 housestaff, over 13 randomly selected dates, to complete a 25‐item survey. Participants (n = 31, 79%) logged a total of 455 hours, reporting 197 pages or telephone requests received regarding medical inpatients. Of these, 41 pages (21%) required a volume status assessment. Participants reported their volume status assessment competency to be moderate (median score = 3, interquartile range = 3 to 4, where 1 = not competent to perform independently and 6 = above average competence). In 9 of the 41 assessments (22%), at least 1 barrier was reported in determining volume status. The most commonly reported barriers were conflicting physical examination findings (n = 8, 20%) and suboptimal patient examination (n = 5, 12%). Over 20% of pages regarding admitted medical patients required volume status assessments by medical housestaff. Despite moderate self‐reported competence in the ability to assess volume status, barriers such as conflicting physical examination findings and suboptimal patient examinations were present in up to 20% of assessments. Therefore, we urge educators to consider incorporating bedside ultrasound training for volume status into the internal medicine curriculum. Journal of Hospital Medicine 2014;9:727–730. © 2014 Society of Hospital Medicine